Reliability of Health-Related Physical Fitness Tests among Colombian Children and Adolescents : The FUPRECOL Study (2015)
Substantial evidence indicates that youth physical fitness levels are an important marker of lifestyle and cardio-metabolic health profiles and predict future risk of chronic diseases. The reliability physical fitness tests have not been explored in Latino-American youth population. This study’s aim was to examine the reliability of health-related physical fitness tests that were used in the Colombian health promotion “Fuprecol study”. Participants were 229 Colombian youth (boys n = 124 and girls n = 105) aged 9 to 17.9 years old. Five components of health-related physical fitness were measured: 1) morphological component: height, weight, body mass index (BMI), waist circumference, triceps skinfold, subscapular skinfold, and body fat (%) via impedance; 2) musculoskeletal component: handgrip and standing long jump test; 3) motor component: speed/agility test (4x10 m shuttle run); 4) flexibility component (hamstring and lumbar extensibility, sit-and-reach test); 5) cardiorespiratory component: 20-meter shuttle-run test (SRT) to estimate maximal oxygen consumption. The tests were performed two times, 1 week apart on the same day of the week, except for the SRT which was performed only once. Intra-observer technical errors of measurement (TEMs) and inter-rater (reliability) were assessed in the morphological component. Reliability for the Musculoskeletal, motor and cardiorespiratory fitness components was examined using Bland–Altman tests. For the morphological component, TEMs were small and reliability was greater than 95% of all cases. For the musculoskeletal, motor, flexibility and cardiorespiratory components, we found adequate reliability patterns in terms of systematic errors (bias) and random error (95% limits of agreement). When the fitness assessments were performed twice, the systematic error was nearly 0 for all tests, except for the sit and reach (mean difference: -1.03% [95% CI = -4.35% to -2.28%]. The results from this study indicate that the “Fuprecol study” health-related physical fitness battery, administered by physical education teachers, was reliable for measuring health-related components of fitness in children and adolescents aged 9–17.9 years old in a school setting in Colombia.